Increasing Community Participation in Village Development through BUMDesa Management in East Java - Maryunani, Maryunani (AIBPM Publisher, 2023)
The objective of this study was to find out how to increase community participation in village development through BUMDesa in several villages in East Java. Recent literature has reported that with village autonomy, the community is a subject that determines the success of development in the village. This research wants to examine how community participation contributes to development in villages with mountainous and coastal topography. Sustainable Livelihood Approach (SLA) were used to increase understanding of people's lives through five types of capital: human, natural, physical, social, and financial. This research found that The participation of upland, lowland and coastal communities has different characters, but there are similarities in motivation to participate in building villages based on research results in six villages including increased income, community institutions (to oversee the management of BUMDesa and villages; existence the witness system, increasing relations or a wider network and the community feeling that they are actively involved in trainings held both by the village government and by BUMDesa. The results indicate that the forms of community participation in village development through BUMDesa can be greatly influenced by the character of the region which ultimately affects the pattern of the economy and livelihood of the community